ANALISIS KESULITAN BELAJAR SISWA PADA MATERI SISTEM SARAF MANUSIA - Sigalingging, Devi Masittah; Kurniawan, Fery; Dongoran, Misahradarsi (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2025)
The purpose of this research is to contribute new knowledge, the contribution of this research is expected to increase our understanding of the factors that affect learning difficulties in the context of certain scientific materials, such as the human nervous system. This type of research uses a descriptive qualitative method. This research tool is observation, interview and documentation. The result of this research is a lot of complicated scientific terms, lack of interesting learning media. Students have difficulty in understanding the mechanism of impulse transmission, students have difficulty in understanding the material concept of human nervous system, and have difficulty in applying the knowledge. This learning difficulty is caused by several factors, namely the complexity of the human nervous system material, low student interest and motivation, lack of intelligence possessed by students, inappropriate learning styles, lack of supporting media, student learning habits, minimal allocation given, absence of peer tutors, the busyness of teachers as deputy principals causes teachers to rarely enter the classroom, low student confidence, health that affects student learning outcomes, lack of attention from parents, low economic factors, school background that previously affected student learning activities. Efforts that can be made to overcome students' difficulties in learning human nervous system material are to improve their understanding of basic concepts by using relevant analogies and examples, increase learning motivation by making learning active and fun, improve learning skills by teaching students effective learning techniques, improve cooperation between teachers, parents and students.